Formasio Iman Anak Melalui Program Bina Iman : Pendekatan untuk Membentuk Karakter Kristiani - Veronika Nato Kolin; Emmeria Tarihoran (Lembaga Pengembangan Kinerja Dosen, 2025)
Children's faith education is an important foundation in developing Christian character, especially in the context of the family and church community. The background to this problem arises from the need to prepare the younger generation to be able to confront the difficulties of the times, especially in the complex digital era. The aim of this study was to assess effectiveness. A faith development program run by the Catholic Church to strengthen children's faith. The methods used include qualitative analysis through interviews and observation of program activities, involving children, parents and church administrators. The research results show that the faith formation program has succeeded in increasing children's understanding of Christian values ​​such as love, forgiveness and honesty, as well as building a strong foundation for their spiritual life. Additionally, this program also plays a role in strengthening the church community and society by involving families in the learning process. Through a series of specially designed activities, children not only understand the basics of faith and religious teachings, but also develop spiritual skills and a closer relationship with God. In this way, the faith development program has proven to be effective in forming children's Christian character from an early age.